Peningkatan keterampilan membaca nyaring menggunakan media flipbook peserta didik kelas II SD - Rosalinda, Ayu Septi; Winarni, Retno (Universitas Sebelas Maret, 2026)
Abstract. Language is one of the important things for every individual. Language components include listening skills, speaking skills, reading skills, and writing skills. The phenomenon that occurs in students is that they are not yet fluent in reading and cannot apply correct punctuation when reading. The purpose of this study was to determine the improvement in reading aloud skills through flipbook media for class II students of SDN 2 Jatipuro in the 2024/2025 academic year. This research is a Classroom Action Research (CAR). The research was conducted for 3 months and involved 16 class II students of SDN 2 Jatipuro. Data collection techniques used observation, interviews, tests, and documentation. Cycle I obtained a completeness of 62.25% with an average of 72.1% included in the good category, but had not reached the research performance indicators. Cycle II obtained an increase of 81.25% with an average of 85.7% included in the very good category. Based on the description above, it can be concluded that the use of flipbook media can improve the reading aloud skills of class II students of SDN 2 Jatipuro in the 2024/2025 academic year.